Relevancia de la toxicología en el esclarecimiento de los homicidios (2014)
Forensic toxicology as its etymology suggests, comes from the Greek ""Toxicon"" meaning poison and ""logos"" meaning speech or treaty, while forensic comes from the ""forum"" Latin referring to the square or space where justice was administered, therefore defined as science that study the poisons and their presence in the human body. Undeniably the input and help of this science for criminal investigations and therefore for an effective and fair administration of justice, especially in regard to criminal jurisdiction given under the beds of relatively recent adversarial criminal justice system, without prejudice to its applicability and usefulness in others fields of jurisdiction. We believe that human resources are vital in this dynamic, because the capacitation, ability, professionalism and experience applied to scientific technical methodologies in unison collaboration with the various sciences and forensic disciplines are indispensable to clarify the facts, supported under a strengthened and reliable evidentiary support for establishing or waive criminal responsibility, authorship and exercise the respective punitive dosimetry if giving rise to it. This not underestimate the importance which must have a suitable high-level technical infrastructure. As it pertains to the case that we are studying is clear the importance of forensic toxicology for proper and successful resolution of the case in comment is necessary, since according to the forensic analysis practiced and other evidence could be established with clarity mobile, ""modus operandi"" and the likely ""criminis"" itself ""iter"" which deployed the alleged perpetrator, bead discovering an alleged earlier murder presumably executed by the same subject, argument to delve into reasons of the importance of that forensic science. Is important to bring out that an optimal and professional inquiry and criminal investigation indicted by the competent authority, that our legislation is the Judicial Police (art. 201 and 202 of Act 906 of 2004) supported by the scientific technical body (INMLCF, Judicial Police art 204 and following of the aforementioned Law) is the probative pillar of an effective criminal prosecution, of course I adhered to the guidelines, legal requirements and controls to ensure the legality and authenticity of the collection, conveyance, transfer, practice, analysis and incorporation of meticulously evidence, leading to an impartial and objective knowledge of the judge, in harmony with the principles of sameness and due process enshrined in Art. 29 of the Political Constitution "